Plants Grown in Parafilm-Wrapped Petri Dishes Are Stressed and Possess Altered Gene Expression Profile - Xu, Le; Li, Shengjie; Shabala, Sergey; Jian, Tao; Zhang, Wenying (Frontiers in Plant Science, 2019)
Arabidopsis is used as a model species in numerous physiological and genetic studies. Most of them employ parafilm-wrapped sterile culture. Here we demonstrate that this method is prone to potential artefacts and can lead to erroneous conclusions. We compared the effect of different sealing methods including air-permeable paper tape and traditional parafilm on Arabidopsis seedling growth, root development and gene expression network. Although seedlings grown in Petri dishes after one week sealed with paper tape showed a similar growth phenotype to that of parafilm-sealed seedlings, more than 700 differentially expressed genes (DEG) were found, including stress and nutrition-responsive genes. In addition, more H2O2 was accumulated in the tissues of parafilm-sealed plants. After 14 days of growth, paper tape-sealed plants grew much better than parafilm-sealed ones and accumulated higher chlorophyll content, with 490 DEGs found. Paper tape-sealed plants grew much better than parafilm-sealed ones after 3 weeks of growth, and higher chlorophyll content was found compared to that of parafilm-sealed seedlings; and only 10 DEGS were found at this stage. Thus, the obvious phenotype observed at the latter stage was a result of differential gene expression at earlier time points, mostly of defence, abiotic stress, nutrition, and phytohormone-responsive genes. More O2 content were detected in paper tape-sealed Petri dishes at early growth stage (7 day), and distinct difference in the CO2 content was observed between parafilm-sealed and paper tape-sealed Petri dishes. Furthermore, the carbon source also influenced seedlings growth with different sealing methods. In conclusion, conventional sealing using parafilm was not the optimal choice, most likely because of the limited gas exchange and a consequent stress caused to plants.